1976
DOI: 10.1007/bf01348017
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus infection in lambs: Studies on passive protection

Abstract: Gnotobiotic lambs were protected against rotavirus infection by the presence in the gut at the time of infection of colostrum or serum containing antibodies to rotavirus. This protection was observed even when passively-acquired antibody was not present in the serum of the infected lamb. Infection under these conditions may have conferred immunity to subsequent challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(73 citation statements)
references
References 9 publications
5
68
0
Order By: Relevance
“…The demonstration of rotavirus replication in phagocytic cells agrees with reports by different investigators who described the presence of rotavirus particles in subepithelial phagocytic cells, suggesting that this may be a mechanism of virus interaction with the immune system (5)(6)(7)13,14). The observation of rotavirus replication in phagocytic cells but the absence of viral replication in MA-104 cells inoculated with the lysate of these phagocytic cells suggests the production of defective viral particles.…”
supporting
confidence: 90%
“…The demonstration of rotavirus replication in phagocytic cells agrees with reports by different investigators who described the presence of rotavirus particles in subepithelial phagocytic cells, suggesting that this may be a mechanism of virus interaction with the immune system (5)(6)(7)13,14). The observation of rotavirus replication in phagocytic cells but the absence of viral replication in MA-104 cells inoculated with the lysate of these phagocytic cells suggests the production of defective viral particles.…”
supporting
confidence: 90%
“…Furthermore, evidence now suggests that rotaviruses may also be involved in causing severe gastroenteritis in adults, particularly the very old (Echeverria et al, 1983;Cubitt & Holzel, 1980). These observations have stimulated work on vaccines against rotavirus infection (Snodgrass & Wells, 1976;Sheridan et al, 1983 ;Vesikari et al, 1984). However, effective vaccines depend on a detailed understanding of the epidemiology of the disease and extent of viral antigenic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The success of a parenteral vaccine might be determined by whether levels of circulating antibodies induced by the vaccine could also induce local protective immunity in the gut. Past studies with a variety of animal models have examined the relative importance of local and systemic antibodies in protection against rotavirus disease and infection (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Some studies using passive immunization strategies have concluded that antibodies in the lumen of the small intestine were the primary determinant of resistance to rotavirus disease and that circulating serum antibodies failed to protect (19,(22)(23)(24).…”
mentioning
confidence: 99%
“…Past studies with a variety of animal models have examined the relative importance of local and systemic antibodies in protection against rotavirus disease and infection (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Some studies using passive immunization strategies have concluded that antibodies in the lumen of the small intestine were the primary determinant of resistance to rotavirus disease and that circulating serum antibodies failed to protect (19,(22)(23)(24). Other studies found that systemic rotavirus antibodies were protective when titers were sufficiently high, perhaps because of transcytosis of antibodies into the lumen of the gut (15,23,24).…”
mentioning
confidence: 99%